Kebisingan, Tingkat Konsentrasi Dan Persepsi Pekerja Penggergajian Kayu Di Pt. Erika Mila Bersama, Sumatera Utara - Muhdi, Muhdi; Syahputri, Yopita; Manurung, Harisyah (Jurnal Penelitian Hasil Hutan, 2023)
Factories usually have several machines to carry out the production process. When working, the machine usually makes a sound due to the use of a bandsaw machine. The aims of this study were to measure the intensity of bandsaw noise, to analyze the effect of bandsaw noise on the concentration level of sawmill workers, and to analyze the effect of noise on workers’ perceptions of sawmills at PT. Erika Mila Bersama, North Sumatra. Measurements were made on 2 bandsaw machines while operating to determine the noise intensity. The concentration test was carried out using a nonparametric test, namely the Wilcoxon test to determine the effect of engine noise on the respondent’s concentration level when using ear protection and without ear protection. Perception test was analyzed using the Linkert scale to determine perception. The results showed that the bandsaw machine noise intensity on machine A and B were 103.22 dB and 104.93 dB respectively. The noise of the band saw machine showed a significant effect on the concentration level of the respondents in the operator of the band saw machine with the two treatments given, while the non-operator respondents showed that the noise had no significant effect on the two treatments given. Perceptions of operators and non-machine operators on noise without ear protection are the same, namely very noisy. After using the earmuff, the machine operator’s perception becomes less noisy and the non-operator’s perception becomes quite noisy. Then when using the earplug the machine operator’s perception is quite noisy and the non-operator’s perception is noisy. The benefit of this research is that it can provide information regarding occupational health and safety regarding the level of concentration of workers on noise and the influence of workers’ perceptions of noise levels and used as evaluation material for companies in carrying out noise control measures at PT. Erika Mila Bersama, North Sumatra.